LOCAL MITIGATION OF PANDEMIC FOR SUSTAINABLE PUBLIC HEALTH ACCORDING TO JAVANESE CULTURE AND BELIEF - Soehadha, Moh; Hamsah, Ustadi (Analisa: Journal of Social Science and Religion, 2022)
Disease prevention is almost always done with a modern approach through medical science or other public health sciences. This approach is the primary reference in mitigating the spread of the disease. In fact, in Indonesian society, there are local wisdoms in the traditions of each ethnic group in tackling the spread of disease, for example, the Javanese tradition. Javanese culture has local wisdom in dealing with pandemics passed down from generation to generation. This study attempts to answer how the mitigation pattern in Javanese culture is. Anthropologically, pandemics can be studied under health anthropology on disease. By taking the case of the Javanese people in Indonesia, this article describes local ways of preventing and overcoming disease outbreaks or mitigating disease outbreaks. The data source of this article is produced from qualitative research through interview techniques, focus group discussions, online seminars, and the study of manuscripts from magazines published in Java. The results showed that local communities, in addition to knowing the causes of disease, also developed ways to prevent and eliminate diseases, and mitigate outbreaks and pandemics. Javanese people see the mitigation of diseases physically and psychically. Physical mitigation tends to be in line with modern medical methods and the application of new normal. The mitigation of psychics is done by using mantras and songs and developing Javanese attitude of “narima ing pandum”  (take it as it comes).